ANALYSIS OF FRESH FRUIT BUNCH (FFB) YIELD LOSSES DUE TO BASE STEM ROT (BPB) DISEASE ATTACKS CAUSED BY GANODERMA BONINENSE IN PT. EVANS GROUP'S PANGKATAN PLANTATION - Agus Sutomo; Khairul Rizal; Yusmaidar Sepriani; Fitra Syawal Harahap (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Oil palm (Elaeis guineensis Jacq.) is a tropical plantation crop with high economic value and is one of Indonesia's mainstay commodities. The purpose of this study was to determine the level of basal stem rot (Ganoderma boninense) infestation in oil palm plants at the Pangkatan Plantation of PT. Evans Group, the magnitude of the resulting fresh fruit bunch (FFB) yield losses, and the relationship between disease severity and the decrease in FFB yield. The research method used was a survey method with a quantitative descriptive approach. The results showed that the level of ganoderma infestation in Block A1 was relatively low at 8.7%, but had a significant impact on oil palm productivity. Trees attacked by ganoderma produced lower fresh fruit bunch (FFB) weights than healthy trees, thus indicating that plant health significantly affects production results.